2014
DOI: 10.1016/j.conb.2014.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive auditory computations

Abstract: The auditory system analyses acoustic signals, extracting their perceptual attributes, and exploiting them to navigate complex auditory environments. While many of the basic transformations that give rise to the early auditory representations are well studied and understood, little is known about the latter cognitive functions that bind, organize, and give meaning to them. They include the ability to attend to, segregate, and track one of many sound sources, to learn its identity, commit it to memory, robustly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 55 publications
(53 reference statements)
2
36
0
Order By: Relevance
“…Such models would need to account for the auditory system's ability to adapt to the demands of an ever-changing acoustic environment and task goals. Recent physiological findings have been amending our views of processing in the auditory system, replacing the conventional view of ‘static’ processing in sensory cortex with a more ‘active’ and malleable mapping that rapidly adapts to the tasks at hand, sound context and listening conditions [11]. Numerous studies have revealed that our auditory experiences can have significant local effects by transforming receptive field properties of individual neurons, and profound global effects by reshaping cortical circuits [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Such models would need to account for the auditory system's ability to adapt to the demands of an ever-changing acoustic environment and task goals. Recent physiological findings have been amending our views of processing in the auditory system, replacing the conventional view of ‘static’ processing in sensory cortex with a more ‘active’ and malleable mapping that rapidly adapts to the tasks at hand, sound context and listening conditions [11]. Numerous studies have revealed that our auditory experiences can have significant local effects by transforming receptive field properties of individual neurons, and profound global effects by reshaping cortical circuits [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Training ferrets to engage in auditory-cued selective attention tasks can produce rapid changes in the spatiotemporal receptive fields of individual neurons in A1 that persist for hours (Fritz et al 2003). Similarly, during performance of an auditory discrimination task these neurons can be seen to temporarily alter their adaptation properties to enhance the differences in response between relevant stimuli (Atiani et al 2014;Shamma and Fritz 2014;Yin et al 2014). It remains unclear whether these comparatively brief changes during auditory tasks reflect longerterm plasticity that allows the circuit to operate in different taskspecific "modes," or if this short-term response plasticity is mechanistically related to that seen with longer-term remapping at all.…”
Section: Associative Plasticity In the Auditory Systemmentioning
confidence: 99%
“…From the seminal studies of Scheich and colleagues (Brosch et al 2011;Ohl and Scheich 2005) and Weinberger and colleagues (Weinberger 2004(Weinberger , 2007(Weinberger , 2015, it is becoming clearer that sensory cortices, such as the auditory cortex, participate in the formation and maintenance of emotional memories, and that the role played by these structures in emotional memory goes beyond simple sensory stimuli perception and memorization (reviewed in Fritz et al 2007;Grosso et al 2015a;Shamma and Fritz 2014;Weinberger 2004Weinberger , 2007Weinberger , 2015. In support of this notion, we have identified higher order components of sensory cortices, such as the temporal auditory cortex Te2, which are essential for storing remote fearful memories (Cambiaghi et al 2015;Grosso et al 2015b;Sacco and Sacchetti 2010).…”
Section: Introductionmentioning
confidence: 99%